A criação de suvenir para o município de Santa Maria, RS: releitura iconográfica do patrimônio histórico-cultural da cidade - Silva, Elizandra Quevedo da (2019)
This study deals with the existence of souvenirs of travel or souvenir in the municipality of Santa Maria, Rio Grande do Sul. The suvenir as subject of this study is justified by the relevance of this object as an essential element in the development of tourism and able to develop the chain identity and belonging through the cultural heritage of the city. At the same time, it was observed that in the county seat there are no specific places to sell souvenir. Based on these premises, this research verified the existence of the souvenir as a representative and significant value in the cultural representation of the municipality. For that, a bibliographical research was carried out, covering some topics about the municipality of Santa Maria, and concepts about tourism, cultural patrimony and souvenir. In the methodology developed exploratory field surveys and data collection through questionnaires and interviews. After the development of the methodology will be developed the final product: the souvenir. Finally, discussions and conclusions will be presented. All research will be directed towards the recognition and appreciation of the cultural heritage of the city of Santa Maria through strategies capable of fostering and leveraging tourism in the municipality.